Association between prenatal exposure to PM2.5 and the increased risk of specified infant mortality in South Korea - Jung, Eun Mi; Kim, Kyoung Nam; Park, Hyesook; Shin, Hwashin H.; Kim, Hae Soon; Cho, Su Jin; Kim, Soon Tae; Ha, Eun Hee (Environment International, 2020)
Background: Findings from previous studies on the association between exposure to fine particulate matter (PM2.5) and the risk of infant mortality were inconsistent. Thus, two main objectives of our study were to examine the association between exposure to PM2.5 and specified infant mortality and to identify critical trimesters. Methods: We retrospectively created a birth cohort of singleton full-term infants born in South Korea between 2010 and 2015 using national birth and infant mortality data. The specified causes of infant mortality were circulatory and respiratory diseases, perinatal conditions, congenital anomalies, and sudden infant death syndrome. We performed 1:10 propensity score matching for various exposure windows: each trimester, prenatal, and postnatal (up to age 1). Conditional logistic regression was applied to estimate odds ratios (ORs) and 95% confidence intervals (CIs), while accounting for gestational age, birth weight, maternal education level, season of birth, and regions (metropolitan areas/provinces). We also conducted sex-stratified analyses and used different matching ratios for sensitivity analyses. Results: A total of 2,501,836 births and 761 deaths (0.03%) were identified in the birth cohort. We found an increased risk of infant mortality per 10 µg/m3 increase in PM2.5 exposure during the prenatal period (OR: 1.29, 95% CI: 1.07–1.55). Exposure in the 1st and 2nd trimesters was linked to an elevated risk (OR: 1.19, 95% CI: 1.02–1.37; OR: 1.21, 95% CI: 1.04–1.40). However, no association was shown in the third trimester. PM2.5 exposure in the 1st and 2nd trimesters was associated with elevated male infant mortality, but did not reach statistical significance in female infants. The use of different matching ratios did not significantly affect the results. Conclusion: The study findings suggest that exposure to PM2.5 could affect infant mortality differently by the timing of exposure and sex, which suggests a relation to fetal development. However, further investigations are warranted.
Keywords: Conditional logistic regressions; Confidence interval; Fine particulate matter (PM2.5); Full term infants; Propensity score matching; Statistical significance; Stratified analysis; Sudden infant death syndromes; Air Pollutants; Air Pollution; Female; Humans; Infant; Infant Mortality; Infant, Newborn; Male; Maternal Exposure; Particulate Matter; Pregnancy; Prenatal Exposure Delayed Effects; Republic of Korea; Retrospective Studies; Birth cohort; Fine particulate matter; Infant mortality; Prenatal exposure; South Korea; Trimester of pregnancy